The Implementation of Total Quality Management in Order to Improve Production Performance and Enhancing the Level of Customer Satisfaction. (2015) - Topalović, Snežana
Abstract: Doing business in a competitive and dynamic environment requires companies to continually improve and enhance their business performance and capabilities. One of the key determinants of the survival of the company in such circumstances is the application of total quality management. In recent years, the company management is more focused on total quality management, which leads to maximizing customer satisfaction and loyalty. The aim of this study is focused at examining the attitudes of corporate clients on a variety of elements implemented TQM process, provided by bank. For the study, data were collected using the survey method and the statistical analysis such as correlation and multiple regression analysis. Results of the research point out that top management commitment, courtesy and responsibility towards our customers as significant factors of satisfaction. Study results help bank managers to identify quality elements that need to be improved, to increase the level of customer satisfaction and enhance their business.